Pengaruh Perputaran Kas, Piutang dan Modal Kerja terhadap Likuiditas pada Perusahaan Subsektor Food dan Beverage Yang Terdaftar di BEI - Muhammad Zulkarnain; Yulina Astuti; Erni Wiriani (Jurnal Ekonomi, 2019)
This study aims to determine the effect of cash turnover, accounts receivable turnover and working capital turnover on liquidity in food and beverage companies listed on the Indonesia Stock Exchange. The data is used from 12 sample companies with financial data from 2013-2018. The method of data analysis uses multiple linear regression equations, test (R2) and hypothesis testing. The results of the study note that cash turnover has a positive effect on liquidity in food and beverage companies listed on the Indonesia Stock Exchange. Meanwhile, accounts receivable turnover and working capital turnover negatively affect liquidity in food and beverage companies listed on the Indonesia Stock Exchange. Hypothesis test results simultaneously cash turnover, accounts receivable turnover and capital turnover have a significant effect on liquidity in food and beverage companies listed on the Indonesia Stock Exchange. The t-test results of cash turnover have a significant effect on liquidity in food and beverage companies listed on the Indonesia Stock Exchange. Then accounts receivable turnover has no significant effect on liquidity on food and beverage companies listed on the Indonesia Stock Exchange, while working capital turnover has a significant effect on liquidity on food and beverage companies listed on the Indonesia Stock Exchange. The coefficient of determination (R2) is 0.556450, stating the percentage contribution of cash turnover, accounts receivable and working capital in the regression model of 55.6%.